2021
DOI: 10.1002/1878-0261.13097
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is required for Smo‐dependent signaling and mediates Smo‐targeted treatment resistance and tumorigenesis in Shh medulloblastoma

Abstract: Sonic hedgehog (Shh)-driven medulloblastoma (Shh MB) cells are dependent on constitutive Shh signaling, but targeted treatment of Shh MB has been ineffective due to drug resistance. The purpose of this study was to address the critical role of signal transducer and activator of transcription 3 (STAT3) in Shh signaling and drug resistance in Shh MB cells. Herein, we show that STAT3 is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…STAT3 activity, in turn, represses p21 expression and fosters the formation of colonies in SHH-MB cells. However, the combined treatment with inhibitors targeting both Smo and STAT3 leads to a marked synergistic effect, effectively overcoming drug resistance in Smo antagonist-resistant SHH-MB cells [32]. Our current study further establishes that celastrol induces apoptosis in ONS-76 cells, with notable increases in ROS levels following celastrol treatment.…”
Section: Discussionsupporting
confidence: 65%
“…STAT3 activity, in turn, represses p21 expression and fosters the formation of colonies in SHH-MB cells. However, the combined treatment with inhibitors targeting both Smo and STAT3 leads to a marked synergistic effect, effectively overcoming drug resistance in Smo antagonist-resistant SHH-MB cells [32]. Our current study further establishes that celastrol induces apoptosis in ONS-76 cells, with notable increases in ROS levels following celastrol treatment.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have shown a link between IGFBP2 and STAT3 activity, and STAT3 is known to regulate cell proliferation and EMT phenotypes [ 7 , 33 , 34 , 61 , 71 ]. STAT3 is phosphorylated at tyrosine705 by Janus Kinase family members, which stimulates its homodimerization and nuclear localization, and transcription of EMT-promoting genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that tumor-derived SHH directly acts on TAMs to promote M2 polarization, mediated by the transcription factor Krüppel-like factor 4 (Klf4) ( 28 ). In addition, other signaling pathways are also involved, such as signal transducer and activator of transcription 3 (STAT3), which is necessary to maintain SHH signaling and can enhance macrophage proliferation and survival through multiple pathways ( 29 , 30 ). Augmented M1 recruitment in SHH subgroup was not observed.…”
Section: Discussionmentioning
confidence: 99%